2014
DOI: 10.3109/15376516.2014.881944
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activity of grape juice concentrate in the rat tongue two-stage initiation–promotion protocol induced by 4-nitroquinoline 1-oxide

Abstract: The aim of this study was to evaluate the anti-tumor activity of grape juice concentrate following medium-term oral carcinogenesis assay induced by 4-nitroquinoline 1-oxide (4NQO). A total of 30 male Wistar rats were distributed into five groups, as follows (n = 6 per group): Group 1 - negative control group (non-treated group); Group 2 - received grape juice concentrate at 1% dose by gavage for eight consecutive weeks; Group 3 - received 4NQO for 8 weeks at 20 ppm dose in drinking water daily; Group 4 - recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…CTRL and Cd groups were treated with drinking water by gavage during the same experimental period. The grape juice group was not included into this experimental design because our research group has evaluated the protective potential of grape juice under different paradigms and the results have revealed that animals treated with grape juice only did not change such biological parameters investigated (Pires et al 2013;Paiotti et al 2013;de Jesus et al 2014).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…CTRL and Cd groups were treated with drinking water by gavage during the same experimental period. The grape juice group was not included into this experimental design because our research group has evaluated the protective potential of grape juice under different paradigms and the results have revealed that animals treated with grape juice only did not change such biological parameters investigated (Pires et al 2013;Paiotti et al 2013;de Jesus et al 2014).…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Also, there is meager information on the diversity of beneficial compounds of muscadine grapes. The variety in structure and phytochemical composition indicate that these compounds may have a potential anticancer activity by acting on various cellular processes linked to tumor development (34). Therefore, in the present study, the antioxidant/anticancer activity of extracts from a wide array of genotypes from muscadine grapes was investigated in TNBC cells.…”
mentioning
confidence: 99%
“…Polyphenols including flavonoids and tannins are the most common bioactive compounds found in M. caesalpi-niifolia. Such agents are able to inhibit tumour development in vivo and in vitro [16][17][18]. This is because polyphenols contain high polarity, and high solubility in polar solvent [19].…”
Section: Discussionmentioning
confidence: 99%